Protein Tyrosine Phosphatase Receptor Type D Regulates Neuropathic Pain After Nerve Injury via the STING-IFN-I Pathway - Sun, Chengkuan; Wu, Guangzhi; Zhang, Zhan; Cao, Rangjuan; Cui, Shusen (Frontiers in Molecular Neuroscience, 2022)
Neuropathic pain is usually caused by injury or dysfunction of the somatosensory system, and medicine is a common way of treatment. Currently, there are still no satisfactory drugs, like opioids and lidocaine, which carry a high risk of addiction. Protein tyrosine phosphatase receptor type D (PTPRD) is a known therapeutic target in addiction pathways and small molecule inhibitors targeting it, such as 7-BIA, have recently been developed to tackle addition. PTPRD is also upregulated in the dorsal root ganglia (DRG) in a rat model of neuropathic pain, but is not yet clear whether PTPRD contributes to the development of neuropathic pain. Here, we established a chronic constriction injury (CCI) and evaluated PTPRD expression and its association with neuropathic pain. PTPRD expression was found to gradually increase after CCI in DRGs, and its expression was concomitant with the progressive development of hypersensitivity as assessed by both mechanical and thermal stimuli. Both PTPRD knockdown and administration of PTPRD inhibitor 7-BIA alleviated CCI-induced neuropathic pain while upregulating STING and IFN-α in the DRG. Treatment with H-151, a STING inhibitor, abolished the analgesic effects of PTPRD knockdown. Taken together, our study suggests that increased levels of PTPRD in the DRG following CCI are involved in the development of neuropathic pain via the STING-IFN-I pathway. 7-BIA, a small molecule inhibitor of PTPRD with anti-addiction effects, may represent a novel and safe therapeutic strategy for the clinical management of neuropathic pain without the risk of addiction.